2020
DOI: 10.1111/jce.14386
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the prevalence and diversity of localized thinning of the left ventricular apex

Abstract: Background The left ventricular apex commonly has a paper‐thin structure. However, available data about its structure are limited to variable samples, methodologies, and results. Objective To investigate the structural anatomy of the left ventricular apex using living heart datasets with the latest computed tomography scanner. Methods One hundred thirty‐one consecutive patients (median age, 73 years; 58% men) who underwent cardiac computed tomography were retrospectively analyzed. Patients with severe aortic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This suggests that apical crypts may have different characteristics from crypts in other areas. Previous studies have reported LV apical thinning as a normal anatomical variation that is distinct from the LV crypt (23,24). However, there may be some overlap, requiring further research to assess the prevalence and location of LV crypts, particularly at the LV apex.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that apical crypts may have different characteristics from crypts in other areas. Previous studies have reported LV apical thinning as a normal anatomical variation that is distinct from the LV crypt (23,24). However, there may be some overlap, requiring further research to assess the prevalence and location of LV crypts, particularly at the LV apex.…”
Section: Discussionmentioning
confidence: 96%
“…The median thickness of the thinnest portion of the LVATP and area in those with severe AS were 1.2 and 3.9 mm 2 . Yamamoto et al 32 noted some significant differences when comparing individuals with AS with individuals without AS (but not in terms of thickness of the thinnest region). The thickness of the thinnest part of LVATP and the distribution of its value among individuals are comparable with the values presented in previous studies.…”
mentioning
confidence: 99%